The Significance Level of Critical Success Factors Affecting Contractor Performance in Winning Public Construction Tenders - Memed Timang Palembangan; Israel Padang (Jurnal Impresi Indonesia, 2026)
This study analyzes the Critical Success Factors (CSFs) influencing contractor performance in public construction tendering under the Ministry of Public Works in Indonesia. Using a quantitative approach and Structural Equation Modeling–Partial Least Squares (SEM-PLS), data were collected from 597 contractors, comprising 161 small, 187 medium, and 249 large firms. The results reveal that the significance of CSFs varies across contractor classifications. For small contractors, performance is significantly influenced by Equipment Resources (X2), Technology and Innovation (X4), Competitive Pricing (X6), and Regulatory Understanding (X7). For medium contractors, the most influential factors are Company Qualification (X1), Equipment Resources (X2), Human Resources (X3), Document Quality (X5), and Competitive Pricing (X6). Meanwhile, for large contractors, performance is mainly driven by Equipment Resources (X2), Technology and Innovation (X4), Document Quality (X5), Competitive Pricing (X6), and Regulatory Understanding (X7). Across all classifications, Competitive Pricing and Equipment Resources consistently emerge as key determinants of tender success. The model fit indices (NFI = 0.712–0.759) confirm the robustness and validity of the developed models. These findings provide empirical evidence of how CSFs differ by organizational scale, offering theoretical contributions to construction management research and practical insights for improving competitiveness, transparency, and efficiency in Indonesia’s public procurement system.